Participatory Approaches’ Operationalization on Scaling-Up Black Soldier Fly Larvae as An Alternative Protein Source for Livestock Feed - Nansamba, Phionah; Nassimbwa, Florence (Student's Journal of Health Research Africa, 2023)
Demand for proteins has increased beyond supply due to the duo competition between humans and animals. Flora and fauna are depleted for proteins used in livestock feeds, this has raised production costs. Current protein insecurity can be solved by the black soldier fly larvae technology that uses organic waste to produce nutritive biomass rich in proteins. However, the innovation has not scaled up among farmers even though participatory approaches have always been employed to scale up different agricultural innovations.